(untitled) (Research, Society and Development, 2018)
Incluir o resumo em inglês. This article aims to elaborate a diagnosis of a not dangerous waste collection organization, that seeks to analyze which factors determine the quality of life of the employees of the organization. Nadler and Lawler (1983) affirm that Quality of Life at Work is a way of thinking about individuals, work and the company itself. This research is characterized as exploratory, descriptive and quantitative with the use of statistics and application of a questionnaire aiming to identify the Quality of Life at Work of this specific company. The questionnaire applied was created through the interpretation and analysis of the eight dimensions of QWL presented by Walton (1973). As for the population, an intentional sample was used, comprising the employees of the administrative sector. As for the analysis carried out from the graphs, it was verified that the organization provides a good quality of life to its employees, since just a small percentages of respondents did not agree in part or did not agree with some of the affirmative questions obtained.